Potential Trace Metal Co-Limitation Controls on N2 Fixation and NO3- Uptake in Lakes with Varying Trophic Status - Romero, Isabel C.; Klein, Nick J.; Sanudo-Wilhelmy, Sergio A.; Capone, Douglas G. (Frontiers in Microbiology, 2013)
The response of N2 fixation and NO3- uptake to environmental conditions and nutrient enrichment experiments in three western U.S. lake systems was studied (eutrophic Clear Lake; mesotrophic Walker Lake; oligotrophic Lake Tahoe). We tested the effect of additions of bioactive trace metals iron (Fe) and molybdenum as Mo(V)), as well as phosphate (P), on these two processes, and carbon fixation, Chl a and bacterial cell counts under both natural conditions and in mesocosm experiments. We found distinct background N2 fixation and NO3- uptake rates: highest at Clear Lake (N2 fixation: 44.7 ± 1.8 nmol N L-1 h-1), intermediate at Walker Lake (N2 fixation: 1.7 ± 1.1 nmol N L-1 h-1; NO3- uptake: 113 ± 37 nmol N L-1 h-1), and lowest at Lake Tahoe (N2 fixation: 0.1 ± 0.07 nmol N L-1 h-1; NO3- uptake: 37.2 ± 10.0 nmol N L-1 h-1). N2 fixation was stimulated above control values with the addition of P and Fe in Clear Lake (up to 63% and 50%, respectively); with Mo(V), Fe, and P in Walker Lake (up to 121%, 990% and 85%, respectively); and with Mo(V) and P in Lake Tahoe (up to 475% and 21%, respectively). NO3- uptake showed the highest stimulation in Lake Tahoe during September 2010, with the addition of P and Mo(V) (~84% for both). High responses to Mo (V) additions were also observed at some sites for carbon fixation (Lake Tahoe: 141%), Chl a (Walker Lake: 54% and Clear Lake: 102%) and bacterial cell counts (Lake Tahoe: 61%). Overall our results suggest that co-limitation of nutrients is probably a common feature in lakes, and that some trace metals may play a crucial role in limiting N2 fixation and NO3- uptake activity, though primarily in non-eutrophic lakes.